Current State in Cryopreservation of Asporogenic and Anaerobic Bacteria - Vysekantsev, I. P.; Gurina, T. M.; Kirilyuk, A. L.; Kudokotseva, E. V.; Biryukova, S. V. (Problems of Cryobiology and Cryomedicine, 2008)
The cryopreservation conditions for asporogenic anaerobic bacteria of different genera have been experimentally established. The H3TA medium provides a high viability at experimental conditions with adding DMSO and thiourea. The storage of samples at temperature of liquid nitrogen during 5 years (observation term) had no effect on initial biological properties of bacteria.